2000
DOI: 10.1897/1551-5028(2000)019<2457:gatoai>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and Toxicity of Aluminum in the Saguenay River, Québec, Canada, in Relation to Discharges From an Aluminum Smelter

Abstract: Abstract-The transformation of bauxite to alumina, the first step in the production of metallic aluminum (Al), generates Al-rich effluents. One installation is located near Jonquière (QC, Canada), with the effluents being discharged into the Saguenay River. We undertook an integrated geochemical and ecotoxicological study to determine if these Al discharges affected the receiving water. In the spring, summer, and autumn of 1997, samples of river water were collected from stations upstream and downstream of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…1), extending 165 km long from Lac Saint-Jean to Tadoussac and having a mean discharge of 1194 m 3 s −1 (Bélanger, 2003), is the principal tributary of the St. Lawrence estuary. Seasonal variations in both discharge rate and water quality tend to be equalized due to regulation by hydropower dams in the upper reach of the river (Schafer et al, 1990;Roy et al, 2000). The Saguenay River intersects the St. Lawrence estuary near Tadoussac, where tides can propagate upriver to ∼ 15 km upstream of Chicoutimi.…”
Section: Study Site and Sample Collectionmentioning
confidence: 99%
“…1), extending 165 km long from Lac Saint-Jean to Tadoussac and having a mean discharge of 1194 m 3 s −1 (Bélanger, 2003), is the principal tributary of the St. Lawrence estuary. Seasonal variations in both discharge rate and water quality tend to be equalized due to regulation by hydropower dams in the upper reach of the river (Schafer et al, 1990;Roy et al, 2000). The Saguenay River intersects the St. Lawrence estuary near Tadoussac, where tides can propagate upriver to ∼ 15 km upstream of Chicoutimi.…”
Section: Study Site and Sample Collectionmentioning
confidence: 99%
“…The chemistry between reactive metal atoms such as Ag, Mg, and Al and organic molecules is relevant in multiple scientific contexts, including organometallic chemistry in the condensed and gas phases, biological systems, interstellar media, and geochemistry. , Indeed, numerous studies on the reactions of such metals with small organic molecules have been reported in the literature. These are typically performed on matrix-isolated metal atom–organic pairs or on gas-phase metal cation–organic pairs. Extensive theoretical work has also been published on such reactions. Although this previous body of work documents the ability to study reaction chemistry of these reactive metals with organics, all previous studies have been restricted to one or two metal atoms or cations reacting with a single organic molecule.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry between reactive metal atoms such as Ag, Mg, and Al and organic molecules is relevant in multiple scientific contexts, including organometallic chemistry in the condensed 1À6 and gas phases, 7À10 biological systems, 11 interstellar media, 12À14 and geochemistry. 15,16 Indeed, numerous studies on the reactions of such metals with small organic molecules have been reported in the literature. These are typically performed on matrix-isolated metal atomÀorganic pairs 17À19 or on gas-phase metal cationÀorganic pairs.…”
Section: ' Introductionmentioning
confidence: 99%
“…This is especially the case where the manufacture of phosphoric acid and phosphate fertilizers occurs (Van Craenenbroeck and Marivoet, 1987). Other potential F contamination sources include the fluoridation of drinking water supplies, the application of Fcontaining fertilizers and pesticides, and heavy industries, such as steel, glass, cement, aluminium smelters and power stations (Leece and Scheltema, 1983;Fuge and Andrews, 1988;Skjelkvåle, 1994;Camargo, 1996;Roy et al, 2000). Fig.…”
mentioning
confidence: 99%